Homer and Ugaritic Literature - Campbell, A. F. (1964)
Literary Themes: Helen of Troy and the Epic of Kret; Achilles and Briseis, Kret and Hurrai. Mythological Themes: Mt. Olympus and Mt. Saphon; Hephaestus and Kathir-and-Khasis; Mythology of Divine Succession; Elysian Plain and Field of El; Warlike Goddesses; Fathers of Gods and Men: Zeus and El: Importunate Goddesses. Miscellaneous Parallels: Divine Ancestry; Restraining Goddesses; Verbal Parallels; Catalogue of Ships; Universal Human Phenomena; 1966.